Modeling method for cycle performance of negative electrode material

By studying the relationship between the characteristics of graphite raw materials and the battery cycle performance and establishing a mathematical model, the problem of difficulty in effectively modeling and predicting the cycle performance of lithium-ion battery negative electrode materials in the existing technology is solved, and accurate prediction and failure analysis of the battery cycle life are achieved.

CN119959093APending Publication Date: 2025-05-09中汽新能(天津)电池科技有限公司
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510048529.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-05-09

AI Technical Summary

Technical Problem

The prior art is difficult to effectively model and predict the cycling performance of lithium-ion battery negative electrode materials, which affects the prediction of the cycle life of the battery and failure analysis.

Method used

By studying the relationship between OI value, graphitization degree, particle size and porosity changes of graphite raw materials and battery cycle performance, a mathematical model is established, and the material structure changes and cycle performance attenuation are analyzed to predict the battery cycle life.

Benefits of technology

It realizes the analysis of the structural changes and cycle performance decay of the negative electrode material from the aspect of material intrinsics, which can be used to analyze the causes of battery failure and prediction of battery cycle life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119959093A_ABST
    Figure CN119959093A_ABST
Patent Text Reader

Abstract

The invention discloses a modeling method for cycle performance of a negative electrode material. The modeling method comprises the following steps: synthesizing artificial graphite by adopting a graphite coke raw material; different batteries of the same system are prepared from different artificial graphite; testing the normal-temperature cycle performance of the battery; the method comprises the following steps: fixing cycle times of the battery, discharging electricity, disassembling to obtain a negative pole piece, cleaning, scraping powder, grinding the powder, and carrying out plane polishing to obtain a plane polishing graph; analyzing the plane polishing diagram, calculating the pore distribution number and the pore distribution area, and establishing a porosity distribution model after battery circulation; based on the tested relationship between the cycle life of the lithium ion battery and the aggregate particle size of the first graphite coke raw material, the secondary particle size of the first graphite which is not coated with carbon, the primary particle size of the second graphite which is coated with carbon, the isotropy value of the coke raw material, the graphitization degree and the porosity distribution of the battery after circulation, the cycle life of the lithium ion battery is obtained. And establishing a cycle life SOH mathematical model. According to the invention, material structure change and cycle performance attenuation can be analyzed from the intrinsic aspect of the material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a modeling method for the cycle performance of negative electrode materials. Background Art

[0002] Lithium-ion batteries are the development direction of power batteries. They are high-energy-density batteries that can store electrical energy and are rechargeable. They can provide power for cars and power tools. The life of power batteries is generally between 5 and 20 years. The number of cycles of ternary lithium-ion batteries can normally reach more than 2,000 times, and those with excellent performance can reach more than 3,000 times. The regular cycle life of lithium iron phosphate batteries can reach more than 3,000 times.

[0003] Lithium-ion battery life prediction technology includes physical model-based methods and mathematically driven methods. Physical model-based methods usually include electrochemical models, equivalent circuit models, and empirical degradation models. Data-driven methods do not require in-depth understanding of the internal mechanism of the battery and predict battery life by analyzing test data. Common methods include: linear regression, polynomial regression, exponential decay model, time series analysis, machine learning model, deep learning model, etc. For example, the patent CN113608134B discloses a method for predicting the cycle life and remaining life of a lithium-ion battery. The method calculates the remaining life and battery life of the battery by collecting the number of battery cycles and the battery capacity data after each cycle, the relationship between the electrolyte content and the capacity retention rate, and the electrolyte consumption rate after a short-term battery cycle. In addition, CN112946504A discloses a method for quickly testing the cycle life of a lithium-ion battery. The method charges the battery to a low SOC at a low rate constant current, rapidly consumes lithium to form a denser SEI film, and replaces or partially replaces the long-term standing step of the high-temperature intermittent cycle with a constant voltage charging step, thereby accelerating the side reactions inside the battery and quickly testing the cycle life of the lithium-ion battery. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings and defects of the prior art and provide a modeling method for the cycle performance of negative electrode materials. The present invention tests, experiments and studies the relationship between the OI value, graphitization degree, particle size of different graphite materials, and the change of the surface porosity of graphite particles and the cycle performance of the manufactured battery, establishes a corresponding mathematical model, and finally realizes the modeling of the cycle performance of the negative electrode material of the lithium ion battery, which can analyze the material structure change and the attenuation of the cycle performance from the intrinsic aspect of the material, and can be used to analyze the cause of battery failure and predict the battery cycle life.

[0005] A modeling method for the cycle performance of negative electrode materials, comprising the steps of:

[0006] Synthesize artificial graphite using graphite coke raw materials, artificial graphite includes first type graphite and second type graphite;

[0007] Using different artificial graphites to make different batteries of the same system; testing the room temperature cycle performance of the batteries, and recording the capacity and capacity retention rate of the batteries at different cycle times;

[0008] The battery is discharged after a fixed number of cycles, and the negative electrode is disassembled to obtain a negative electrode sheet; the negative electrode sheet obtained after the disassembly is cleaned, lithium, SBR and CMC are removed, and then the powder is scraped off, and the scraped powder is ground and the ground powder surface is polished to obtain a plane polishing image;

[0009] The plane polishing map is analyzed by using a map analysis software to calculate the number of pore distribution and the pore distribution area; based on the number of pore distribution and the pore distribution area, a porosity distribution model after battery cycling is established;

[0010] A cycle life SOH mathematical model is established based on the relationship between the cycle life of lithium-ion batteries obtained from the test and the aggregate particle size of the coke raw material of the first type of graphite, the secondary particle size of the first type of graphite not coated with carbon, the primary particle size of the second type of graphite coated with carbon, the isotropy value of the coke raw material, the degree of graphitization and the porosity distribution after battery cycling.

[0011] The formation process of the first type of graphite is as follows: the coke raw material of the first type of graphite that meets the preset aggregate particle size requirements is obtained by subjecting the coke to a primary coarse powder making and a secondary fine powder making process; the coke raw material of the first type of graphite is shaped and graphitized, and then screened and iron-removed to obtain the primary particles of the first type of graphite; the coke raw material of the first type of graphite is mixed with asphalt, petroleum by-products and a carbon source, and then high-temperature sintered, and then granulated and crushed and shaped in sequence, and then screened and iron-removed after graphitization to obtain the secondary particles of the first type of graphite: wherein the amount of carbon source added is 5-20%.

[0012] Among them, the second type of graphite formation process is to shape the granulated or ungranulated graphite powder material through powder making, carbonize it through hydrocarbons, asphalt or resin, and then obtain the primary particles of the coated second type of graphite after screening and iron removal; wherein, the surface coating carbonization is carried out in gas phase, liquid phase and solid phase, the carbon source coating amount is 3%-9%, and the coating temperature is 700-1000℃.

[0013] Among them, the graphite coke raw materials include petroleum coke, needle coke, and coal coke; the isotropy of the coke raw materials of the first type of graphite is OI, and the isotropy is characterized by the compressive strength P, flexural strength M and resistivity Re of the coke raw materials.

[0014] Wherein, the isotropy of the coke raw material of the first type of graphite is expressed as follows:

[0015]

[0016] Where M 横 、M 纵 Indicates the transverse and longitudinal flexural strength of the coke raw material of the first type of graphite, P 横 , P 纵 Re represents the transverse compressive strength and longitudinal compressive strength of the first type of graphite coke raw material, Re 横 、Re 纵 The transverse resistivity and longitudinal resistivity of the coke raw material representing the first type of graphite are shown.

[0017] The graphitization degree P of the artificial graphite during the synthesis process is 石墨化度 The expression is as follows:

[0018] P 石墨化度(t) =∫ 0 t C e (τ)dτ+∫ 0 t T e (τ)dτ+∫ 0 t t e (τ)dτ;

[0019] ∫ 0 t C e (τ)dτ represents the effect of the amount of carbon source added C on the degree of graphitization at different times, from the start of the reaction to the end of the reaction; ∫ 0 t T e (τ)dτ represents the effect of reaction temperature T on graphitization degree at different times from the start of reaction to the end of reaction; ∫ 0 t t e (τ)dτ represents the effect of reaction time t on the degree of graphitization from the start of the reaction to the end of the reaction at different times, e is the finished product reaction constant, and τ is the different moments of the reaction.

[0020] Wherein, the porosity distribution model after battery cycling includes:

[0021]

[0022] Where N(x) is the porosity distribution after battery cycling; Represents the effect of the pore distribution area S on the porosity distribution from the beginning to the end of the cycle at different cycle numbers; Represents the effect of the pore distribution quantity Qty on the pore distribution from the beginning to the end of the cycle under different cycle numbers.

[0023] Wherein, the cycle life SOH mathematical model includes:

[0024]

[0025] Where SOH(N) is the effect of graphite pore distribution on the cycle performance of graphite materials. The OI value of the coke raw material for the first type of graphite changes the pore distribution of the material during the cycle. is the change of pore distribution due to the change of graphitization degree during the cycle, The change of the aggregate particle size distribution of the coke raw material for the first type of graphite with the change of the pore distribution as the cycle changes, The particle size distribution of the secondary particles of the first type of graphite changes with the cycle of the pore size distribution, The particle size of the carbonized coated primary particles of the second type of graphite affects the pore distribution with circulation.

[0026] Among them, the particle size distribution of the coke raw material with suitable particle size obtained by powdering or granulating coke is PD, the aggregate particle size range is Dmin-Dmax, the particle size distribution of the secondary particles of the first type of graphite without carbon coating is PD1, and the particle size range is D1min-D1max, and the particle size of the primary particles of the first type of graphite after shaping is PD2, and the particle size range is D2min-D2max; by establishing the mathematical model of {PD(Dmin-Dmax), N(%)}, {PD1(D1min-D1max), N(%)}, {PD2(D2min-D2max), N(%)}, {OI(%), N(%)}, {P(%), N(%)}, the relationship between cycle life and pore distribution number is analyzed, and the cycle life SOH mathematical model is established.

[0027] The disassembled negative electrode sheet is soaked in DMC and ethanol and ultrasonically cleaned, and then scraped to obtain a powder mixed with graphite and a conductive agent. After drying, the scraped powder is ground and flat-polished.

[0028] When the battery is subjected to a cycle test, batteries of the same capacity are placed in a 25° C. incubator and subjected to a cycle test using a 1C current.

[0029] The present invention performs preset cycle tests on batteries made of different graphite materials, performs powder scraping treatment on negative pole pieces of batteries with different cycle times, and establishes a porosity distribution model after battery cycling based on the obtained calculated pore distribution number and pore distribution area by analyzing the plane polishing diagram of the pole piece powder; and establishes a cycle life SOH mathematical model based on the relationship between the cycle life of lithium-ion batteries obtained from the test and the aggregate particle size of coke raw materials, the finished particle size of the first type of graphite, the finished particle size of the second type of graphite coated with carbon, the isotropy value of the coke raw materials, the degree of graphitization and the porosity distribution after battery cycling; thereby, modeling and analysis of the cycle performance of battery negative electrode materials can be achieved.

[0030] The present invention establishes mathematical models of different graphite materials in the cycle process through the types of raw materials such as graphite in negative electrode materials, synthesis processes and graphitization differences, and establishes a mathematical model of the relationship between the pore distribution number and cycle life of graphite materials. The material structure changes and the attenuation of cycle performance are analyzed from the intrinsic aspects of the materials, which can be used to analyze the causes of battery failure and predict the battery cycle life. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 It is a schematic diagram of the synthesis process of the first type of graphite of the present invention.

[0032] Figure 2 This is a particle size distribution diagram of the coke raw material of the first type of graphite of the present invention.

[0033] Figure 3 It is a schematic diagram of the synthesis process of the second type of graphite of the present invention.

[0034] Figure 4 This is a CP-SEM image of the uncoated secondary particle graphite of the first type of graphite in the fresh battery of the present invention.

[0035] Figure 5 This is a CP-SEM image of the uncoated secondary particle graphite of the first type of graphite that has been cycled 1500 times according to the present invention.

[0036] Figure 6 This is a CP-SEM image of uncoated primary graphite particles of the first type of graphite in the fresh battery of the present invention.

[0037] Figure 7 This is a CP-SEM image of uncoated primary graphite particles of the first type of graphite that has been cycled 1297 times in the present invention.

[0038] Figure 8 This is a CP-SEM image of the primary graphite-coated particles of the fresh battery second type graphite of the present invention.

[0039] Fig. 9This is a CP-SEM image of uncoated primary graphite particles of the first type of graphite that has been cycled 1297 times in the present invention.

[0040] Fig.10 It is a normal temperature cycle curve diagram of the secondary particle graphite of the first type of graphite of the present invention.

[0041] Fig.11 This is a normal temperature cycle curve diagram of uncoated single-particle graphite of the first type of graphite of the present invention.

[0042] Fig.12 It is a normal temperature cycle curve diagram of a single-particle graphite coating of the second type of graphite of the present invention. DETAILED DESCRIPTION

[0043] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0044] A modeling method for the cycle performance of a negative electrode material according to an embodiment of the present invention comprises the following steps:

[0045] Synthesize artificial graphite using graphite coke raw materials, artificial graphite includes first type graphite and second type graphite;

[0046] Using different artificial graphites to make different batteries of the same system; testing the room temperature cycle performance of the batteries, and recording the capacity and capacity retention rate of the batteries at different cycle times;

[0047] The battery is discharged after a fixed number of cycles, and the negative electrode is disassembled to obtain a negative electrode sheet; the negative electrode sheet obtained after the disassembly is cleaned, lithium, SBR and CMC are removed, and then the powder is scraped off, and the scraped powder is ground and the ground powder surface is polished to obtain a plane polishing image;

[0048] The plane polishing map is analyzed by using a map analysis software to calculate the number of pore distribution and the pore distribution area; based on the number of pore distribution and the pore distribution area, a porosity distribution model after battery cycling is established;

[0049] A cycle life SOH mathematical model is established based on the relationship between the cycle life of lithium-ion batteries obtained from the test and the aggregate particle size of the coke raw material of the first type of graphite, the secondary particle size of the first type of graphite not coated with carbon, the primary particle size of the second type of graphite coated with carbon, the isotropy value of the coke raw material, the degree of graphitization and the porosity distribution after battery cycling.

[0050] Specifically, the artificial graphite can be produced by using coke raw materials such as petroleum coke, needle coke and coal tar pitch, which are all combustible solid products obtained by coking. The sulfur content is generally below 0.5%.

[0051] Among them, the first type of graphite forming process: Figure 1 As shown in the process, the coke raw material of graphite coke, such as coke, is subjected to a primary coarse powder making and a secondary fine powder making to obtain a coke raw material with an aggregate particle size that meets the preset requirements. The coke raw material is then mixed with a carbon source through asphalt, petroleum by-products, and is sequentially subjected to secondary granulation and crushing after high-temperature sintering. After graphitization, secondary screening and iron removal are performed to obtain secondary particles of the first type of graphite, wherein the amount of carbon source added is 5-20%.

[0052] Specifically, a jaw crusher can be used for coarse crushing, and the coke raw material with a particle size of ≤1200mm can be crushed. The material after crushing has a particle size of 10-350mm, and then it is ground by a grinding machine. The grinding machine can process coke raw materials with a coarse crushing size of ≤25mm, and the material after the first grinding has a particle size of 50-200μm. Then it is subjected to secondary grinding. After the secondary grinding obtained after the treatment is classified, the particle size of the coke raw material after the secondary grinding is 4-20μm. The coke raw material that does not meet the fineness requirement is continuously sent to the grinding machine for grinding until it meets the qualified particle size requirement, and the coke raw material of the first type of graphite with the particle size meeting the requirement is obtained; thereafter, the coke raw material with the particle size meeting the requirement is used for the molding of primary particles and secondary particles of the first type of graphite.

[0053] In addition, the compressive strength P, flexural strength M and resistivity Re of the coke raw material of the first type of graphite under different pressures are tested, and the isotropy thereof is characterized by the compressive strength P, flexural strength M and resistivity Re of the coke raw material under different pressures. The following table shows the values ​​of the compressive strength P, flexural strength M and resistivity Re of the coke raw material of the first type of graphite under different molding pressures.

[0054] Table 1

[0055]

[0056]

[0057] According to the test results in Table 1, according to the coke raw materials of the first type of graphite under different pressures (20Mpa, 40Mpa, 60Mpa, 80Mpa, 100Mpa, 120Mpa), according to the test results of 6 groups of data after the test, the means of (P horizontal / P vertical + M horizontal / M vertical + Re horizontal / Re vertical) / 3 are (0.99, 0.98, 0.99, 1.00, 1.01, 0.99), and the average value under different pressures is 1.00, indicating that the coke forming pressure has little effect on the isotropy of the material, and has a greater correlation with the structure of the coke raw material itself, which can characterize the isotropy of the material. From this, the OI value formula of the coke raw material can be derived as follows:

[0058]

[0059] In the present application, in the first type of graphite formation process, the primary particle graphite forming process is to obtain the coke raw material with the required particle size through shaping, graphitization, screening and iron removal; the secondary particle uncoated carbon process is to mix the coke raw material with the required particle size with asphalt, and the mass mixing ratio is 100: (5-20). The mixed material is transferred to the hopper through the feeder, and the hopper is put into the air mill for grinding, and the particle size of 5-10mm is ground to the corresponding particle size to obtain the coke raw material with suitable particle size, and its particle size distribution is as follows: Figure 2 As shown, the D50 particle size of the material is: 11.453 μm.

[0060] The coke raw material with suitable particle size obtained by the above grinding is put into the reactor for heating and sintering secondary granulation, the air in the reactor is replaced with N2, the reactor is sealed, and electrically heated at a pressure of 20pa, stirred at 200-300℃ for 1-3 hours, and then continued to heat to 400-500℃, stirred to obtain a material with a particle size of 10-20mm, cooled and discharged to obtain an intermediate material of the product; the volatile gas is extracted from the reactor, cooled by a condenser, condensed into liquid for collection, and the gas is filtered and discharged through activated carbon; the intermediate material is transported to a ball mill for mechanical ball milling, 10-20mm material is ground, and then sieved by a screening machine to obtain a suitable aggregate particle size to achieve micro-shaping;

[0061] Graphite materials with suitable aggregate particle sizes are graphitized in an Acheson crucible furnace, negative electrode materials are evenly placed in the graphite crucible furnace, resistor materials are evenly placed on the periphery of the graphite crucible at the furnace core, and then covered with insulation materials to fill the furnace body; after the furnace body is filled, the electrodes on both sides of the graphitization path are energized for heating, the furnace temperature reaches 800°C, the furnace top is covered and a gas collecting hood is set, sintering is performed at different temperatures T, and the graphitization degree P is compared. At high temperatures, the impurities at the edge of the amorphous carbon microcrystalline structure are reduced so that it has a layered crystal structure of graphite, and the graphitization degree P obtained by sintering at different times t is P, and the material is discharged after cooling to room temperature;

[0062] The graphitized material is screened and iron is removed to obtain the first type of graphite product; according to the relationship between the carbon source addition amount %, the sintering temperature T and the constant temperature sintering time t, the graphitization relationship is obtained: as shown in Table 2 below.

[0063] Table 2

[0064]

[0065] According to the relationship in Table 2, the relationship of negative electrode graphitization degree is obtained, which is affected by the addition of different carbon sources at four points with different proportions of carbon content of 5%, 10%, 15%, and 20%; four sintering temperatures of 2200°C, 2400°C, 2600°C, and 2800°C; and the influence of four sintering temperatures of 7 days, 14 days, 21 days, and 28 days, which affect the graphitization degree of the finished product.

[0066] In the embodiment of the present application, the manufacturing process of the second type of graphite is as follows: Figure 3 As shown, the finished graphite powder material is used for coating, and the coating process is to re-powder the graphite powder, and then shape, coat, carbonize, screen, and remove iron to obtain it; liquid phase coating, solid phase coating and gas phase CVD coating can be used, the addition ratio of the carbon source is 3%-9%, the sintering temperature is 700℃-1000℃, and the sintering constant temperature time is 16-24 hours to obtain the finished graphite after carbon coating; according to the relationship between the carbon source addition amount %, the sintering temperature T and the constant temperature sintering time t, the graphitization relationship is obtained, as shown in Table 3.

[0067] Table 3

[0068]

[0069] By comparison, it was found that the addition of four different carbon coatings of 3%, 5%, 7% and 9%, sintering at four different temperatures of 700℃, 800℃, 900℃ and 1000℃, and sintering for different times of 16 hours, 19 hours, 21 hours and 24 hours affected the graphitization degree of the carbon-coated finished products.

[0070] By processing the above data, a calculation formula for the graphitization degree of graphite material in the synthesis reaction is established;

[0071] P 石墨化度(t) =∫ 0 t C e (τ)dτ+∫ 0 t T e (τ)dτ+∫ 0 t t e (τ)dτ.

[0072] By using lithium iron phosphate material for the positive electrode and different graphite materials for the negative electrode, SP4360143 soft-pack batteries with similar capacity were made under the same electrolyte, and the cycle was tested at 25°C. The electrode pores will appear before and after the cycle. After the fresh empty battery is disassembled, the negative electrode is taken out, the electrode is cut into blocks and completely immersed in an ethanol solvent, ultrasonicated for 2 hours, with a 20-minute interval in between, and soaked at room temperature for 24 hours to dissolve the embedded lithium metal. The filtered electrode is dried at 90°C for 3 hours, and then the electrode is immersed in water, and the above ultrasonic steps are repeated to dissolve the SBR and CMC glue of the relevant negative electrode and filter it, using 90°C for drying for 3 hours, and then the electrode is scraped and ground, and the ground powder is plane polished (SEM-CP); the plane polishing diagrams of the first type of graphite and the second type of graphite (primary graphite particles, secondary graphite particles of the first type of graphite, and primary particle-coated graphite of the second type of graphite) before and after the cycle are tested, as shown Figures 4 to 9 As shown, it can be seen from the SEM of the plane polishing after the test that the number and distribution area of ​​pores are calculated by the spectrum analysis software and shown in Table 4 below:

[0073] Table 4

[0074]

[0075] The above table shows that the number and area of ​​pore distribution of fresh secondary graphite particles before and after the cycle are different. Among them, the number of pores and the area of ​​pore distribution of the secondary graphite particles before the cycle of 5000 times are 15 and the distribution area is 4.239μm 2 After 1500 cycles, the number of distributions increased to 18, and the distribution area was 31.793 μm 2 ; The number of pores in the fresh battery primary graphite particles before 5000 cycles is 9, and the pore distribution area is 11.145μm 2 After 1273 cycles, the number of pores is 10 and the pore distribution area is 31.4 μm 2 ; The number of pores in the fresh primary particle-coated graphite before the 5000th cycle is 12, and the pore distribution area is 6.028μm 2 After 1500 cycles, the number of pores is 30 and the pore distribution area is 33.92 μm 2 , the number of pores and the pore distribution area of ​​the same 1000 times test increase proportionally. According to the relationship between the porosity of graphite, the calculation model of porosity distribution is established:

[0076]

[0077] Combined with the product graphitization degree, the finished graphite OI value, the finished graphite particle size distribution of the first type of graphite, and the finished graphite particle size distribution of the second type of graphite, the cycle performance of the negative electrode material of the battery with different negative electrode materials prepared in the above embodiments is calculated, as shown in FIG. Figure 8 As shown, through the comparison of cycle performance, it is found that the capacity retention rate of secondary particle graphite is 97.63% after 1500 cycles. Fig. 9 Single particle without coating cycle 1273 times @ 94.68%, Fig.10 The single-particle coated graphite material was cycled 1500 times @92.39%.

[0078]

[0079] According to the relationship between different graphite particles compared in the above table, the OI values ​​of the coke raw materials of the secondary graphite particles and the primary graphite particles of the first type of graphite are different. The OI value after granulation is 1.0, and the OI value of the primary particles is 1.6, indicating that the secondary particles are more isotropic and conducive to circulation. The graphitization degree of the secondary graphite particles is 93.1%, and that of the primary graphite particles is 92.8%, which is not much different. The aggregate particle diameter and the finished product particle size affect the distribution of porosity. The primary particles of the second type of graphite are coated with graphite, and the graphitization degree of the material is reduced to 92.3%. The OI value of the finished graphite product is 1.3. The influence of aggregate particle size and finished product particle size on the porosity of the material.

[0080] Combining the pore size distribution of the first type of graphite and the second type of graphite before and after recycling, and the relationship between the recycling performance and porosity distribution of the finished graphite, the following model is established:

[0081]

[0082] verify:

[0083] Batteries made of different negative electrode materials using the first type of graphite and the second type of graphite mentioned above were tested to obtain the number and area of ​​pore distribution of negative electrode graphite materials for fresh batteries, batteries with 200, 500 and 1000 cycles, and the relationship between the number and area of ​​pore distribution of the initial negative electrode sheet material and the corresponding different number of cycles and battery capacity retention rate. It can be seen that as the number of cycles increases, the number and area of ​​pore distribution increase in a proportional gradient, and the relationship between the cycle life of the battery and the porosity can be inferred, verifying that the cycle performance of graphite and the porosity distribution model meet the requirements.

[0084]

[0085] The basic principles and main features of the present invention and the advantages of the present invention are shown and described above. It is obvious to those skilled in the art that the present invention is not limited to the details of the above exemplary embodiments, and the present invention can be implemented in other specific forms without departing from the spirit or basic features of the present invention.

[0086] Therefore, the embodiments should be considered in all respects as illustrative and non-restrictive, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is therefore intended that all changes falling within the meaning and range of equivalent elements of the claims are included in the present invention.

[0087] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A modeling method for the cycle performance of negative electrode materials, characterized in that: Includes steps: Synthesize artificial graphite using graphite coke raw materials, artificial graphite includes first type graphite and second type graphite; Using different artificial graphites to make different batteries of the same system; testing the room temperature cycle performance of the batteries, and recording the capacity and capacity retention rate of the batteries at different cycle times; The battery is discharged after a fixed number of cycles, and the negative electrode is disassembled to obtain a negative electrode sheet; the negative electrode sheet obtained after the disassembly is cleaned, lithium, SBR and CMC are removed, and then the powder is scraped off, and the scraped powder is ground and the ground powder surface is polished to obtain a plane polishing image; The plane polishing map is analyzed by using a map analysis software to calculate the number of pore distribution and the pore distribution area; based on the number of pore distribution and the pore distribution area, a porosity distribution model after battery cycling is established; A cycle life SOH mathematical model is established based on the relationship between the cycle life of lithium-ion batteries obtained from the test and the aggregate particle size of the coke raw material of the first type of graphite, the secondary particle size of the first type of graphite not coated with carbon, the primary particle size of the second type of graphite coated with carbon, the isotropy value of the coke raw material, the degree of graphitization and the porosity distribution after battery cycling.

2. The modeling method for the cycle performance of negative electrode materials according to claim 1, characterized in that: The formation process of the first type of graphite is as follows: the coke raw material of the first type of graphite that meets the preset aggregate particle size requirements is obtained by subjecting coke to a primary coarse powder milling and a secondary fine powder milling process; the coke raw material of the first type of graphite is shaped and graphitized, and then screened and iron-removed to obtain the primary particles of the first type of graphite; the coke raw material of the first type of graphite is mixed with asphalt, petroleum by-products and a carbon source, and then high-temperature sintered in sequence, and then granulated and crushed and shaped, and then screened and iron-removed after graphitization to obtain the secondary particles of the first type of graphite: wherein the amount of carbon source added is 5-20%.

3. The modeling method for the cycle performance of negative electrode materials according to claim 2, characterized in that: The second type of graphite formation process is: after the granulated or ungranulated graphite powder material is pulverized and shaped, it is carbon-coated and carbonized by hydrocarbons, asphalt or resin, and then the primary particles of the coated second type of graphite are obtained after screening and iron removal; wherein, the surface coating and carbonization are carried out in gas phase, liquid phase and solid phase, the carbon source coating amount is 3%-9%, and the coating temperature is 700-1000℃.

4. The modeling method for the cycle performance of negative electrode materials according to claim 1, characterized in that: The graphite coke raw materials include petroleum coke, needle coke and coal coke; the isotropy of the coke raw materials of the first type of graphite is OI, and the isotropy is characterized by the compressive strength P, flexural strength M and resistivity Re of the coke raw materials.

5. The modeling method for the cycle performance of negative electrode materials according to claim 4, characterized in that: The isotropy of the coke raw material of the first type of graphite is expressed as follows: Where M 横 、M 纵 Indicates the transverse and longitudinal flexural strength of the coke raw material of the first type of graphite, P 横 , P 纵 Re represents the transverse compressive strength and longitudinal compressive strength of the coke raw material of the first type of graphite, Re 横 、Re 纵 The transverse resistivity and longitudinal resistivity of the coke raw material representing the first type of graphite are shown.

6. The modeling method for the cycle performance of negative electrode materials according to claim 5, characterized in that: The graphitization degree P of the artificial graphite during the synthesis process 石墨化度 The expression is as follows: P Graphitization degree (t) =∫0 t C e (τ)dτ+∫0 t T e (τ)dτ+∫0 t t e (v)dτ; ∫0 t C e (τ)dτ represents the effect of the amount of carbon source added C on the degree of graphitization at different times, from the start of the reaction to the end of the reaction; ∫0 t T e (τ)dτ represents the effect of reaction temperature T on graphitization degree at different times from the start of reaction to the end of reaction; ∫0 t t e (τ)dτ represents the effect of reaction time t on the degree of graphitization from the start of the reaction to the end of the reaction at different times, e is the finished product reaction constant, and τ is the different moments of the reaction.

7. The modeling method for the cycle performance of negative electrode materials according to claim 6, characterized in that: The porosity distribution model of the battery after cycling includes: Where N(x) is the porosity distribution after battery cycling; Represents the effect of the pore distribution area S on the porosity distribution from the beginning to the end of the cycle at different cycle numbers; Represents the effect of the pore distribution quantity Qty on the pore distribution from the beginning to the end of the cycle under different cycle numbers.

8. The modeling method for the cycle performance of negative electrode materials according to claim 7, characterized in that: The cycle life SOH mathematical model includes: Where SOH(N) is the effect of graphite pore distribution on the cycle performance of graphite materials. The OI value of the coke raw material for the first type of graphite changes the pore distribution of the material during the cycle. is the change of pore distribution due to the change of graphitization degree during the cycle, The change of the aggregate particle size distribution of the coke raw material for the first type of graphite with the change of the pore distribution as the cycle changes, The secondary particle size distribution of the first type of graphite changes with the cycle of pore size distribution. The influence of the primary particle size of the carbonized and coated second type graphite on the pore distribution during circulation.

9. The modeling method for the cycle performance of negative electrode materials according to claim 1, characterized in that: The disassembled negative electrode sheet is soaked in DMC and ethanol and ultrasonically cleaned, and then scraped to obtain a powder mixed with graphite and a conductive agent. After drying, the scraped powder is ground and flat-polished.

10. The modeling method for the cycle performance of negative electrode materials according to claim 1, characterized in that: When the battery is subjected to a cycle test, batteries of the same capacity are placed in a 25° C. incubator and subjected to a cycle test using a 1C current.

Citation Information

Patent Citations

  • Method for rapidly testing cycle life of lithium ion battery

    CN112946504A